THE INFLUENCE OF TEAM COHESION AND TRUST ON TEAM EFFECTIVENESS IN PREVENTING TUBERCULOSIS - Sinta Dewi Lestyoningrum; Yuni Purwatiningsih; Debri Rizki Faisal (Indonesian Journal of Health Administration, 2022)
Background: The transmission of tuberculosis (TB) is hard to stop. Surabaya city has the highest TB cases in East Java and only achieved <90% of the target in 2017-2018. The formation of preventing TB team in every primary health care (PHC) is expected to work effectively in preventing TB cases in society. Aims: This study aimed to analyze the impact of cohesion and trust within a team on team effectiveness in preventing TB cases in Surabaya. Methods: This study was an observational study with a cross-sectional design conducted in 43 primary healthcare centers (PHC), and it involved 319 respondents selected by proportional stratified random sampling. The data were collected through questionnaires and tested descriptively and through multivariable linear regression to confirm the most significant models of independent variables and dependent variables. Results: The result showed that task cohesion of the cohesion variable (RR= 0.374; p= 0.014) and cooperative behaviors of the trust variable (RR= 0.558; p= 0.000) had a significant influence on team effectiveness. The others dimension of team cohesion and trust had no significant impact on team effectiveness   Conclusion: Team effectiveness is dependent on team cohesion and trust that the teamwork process component. The Surabaya City Health Office needs to collaborate with the PHC management to evaluate the teamwork of the preventing TB team through in-depth interviews or other methods to get the problem in the team.